Redefining Walrus Stocks in Canada - Stewart, Robert E.A. (ARCTIC, 2009)
Defining management units is basic to the sound management of resources. Walrus (Odobenus rosmarus rosmarus) are hunted throughout their range in Canada and are subject to other human activities requiring management decisions. Current management units are based on a comprehensive review and a stock assessment completed in the mid 1990s. Between 1993 and 2004, satellite-linked radio tags provided information on the movements of walrus in Canada’s High Arctic. These data were incorporated with other information that has become available since 1995 to reassess walrus management units in Canada. Tagging data and other information suggest that some finer discrimination of walrus populations is needed as a precautionary approach and to formulate testable hypotheses. Specifically, the previous North Water/Baffin Bay walrus stock may be considered to be three stocks: Baffin Bay, west Jones Sound, and Penny Strait Lancaster Sound stocks. The Foxe Basin population appears to comprise two stocks (North Foxe Basin and Central Foxe Basin) rather than one. Previously suspected subdivisions in the Hudson Bay-Davis Strait population are substantiated by isotopic evidence although sampling on a finer geographic scale is required before this stock can be partitioned. There is new evidence to support the previously postulated separation of the walrus in the Southern and Eastern Hudson Bay stock from all others, but no evidence to warrant subdivision. La définition des unités de gestion est fondamentale à la bonne gestion des ressources. Le morse (Odobenus rosmarus rosmarus) est chassé dans son aire d’extension au Canada, en plus d’être assujetti à d’autres activités humaines nécessitant des décisions en matière de gestion. Les unités de gestion actuelles sont fondées sur l’examen exhaustif et l’évaluation des groupes effectués vers le milieu des années 1990. Entre 1993 et 2004, des étiquettes radio par satellite ont fourni des renseignements sur les mouvements du morse dans le Grand Nord du Canada. Ces données ont été intégrées ...